Epstein-Barr viral latency is disrupted by the immediate-early BRLF1 protein through a cell-specific mechanism. - Zalani, S (1996)
Epstein-Barr virus (EBV), the causative agent of infectious mononucleosis, is a human herpesvirus associated with epithelial cell malignancies (nasopharyngeal carcinoma) as well as B-cell malignancies. Understanding how viral latency is disrupted is a central issue in herpesvirus biology. Epithelial cells are the major site of lytic EBV replication within the human host, and viral reactivation occurs in EBV-associated nasopharyngeal carcinomas. It is known that expression of a single viral immediate-early protein, BZLF1, is sufficient to initiate the switch from latent to lytic infection in B cells. Cellular regulation of BZLF1 transcription is therefore thought to play a key role in regulating the stringency of viral latency. Here we show that, unexpectedly, expression of another viral immediate-early protein, BRLF1, can disrupt viral latency in an epithelial cell-specific fashion. Therefore, the mechanisms leading to disruption of EBV latency appear to be cell-type specific.